PENGGUNAAN KOMPONEN PEMBENTUK PAJAK TANGGUHAN DALAM MENDETEKSI MANAJEMEN LABA - Irreza, Irreza; Yulianti, Yulianti (UI Scholars Hub, 2012)
This study is intended to investigate whether the components that constitute deferred tax expense can be a better detector of earnings management activity in Indonesian capital market. There is a possibility that not all information contained in deferred tax expense can be used as detector of earnings management. To analyze that, this study divided deferred tax components into acrued revenues and expenses, employee compensation, depreciation of tangible assets, valuation of other assets, and miscellaneous items. Using the income distribution model (Burghstahler and Dichev 1997) for a 10 year period, we found that the total change in net deferred tax liabilities, total accruals and only depreciation component have a significant impact in detecting earnings management activities to avoid losses. These findings show the importance of deferred tax disclosure for financial statement users – especially in detecting earnings management activity, and also create a new direction in deferred tax study in Indonesia to focus more on the components that constitute deferred tax.